Grand Opening of New Fresno County Jail at M and Merced Streets - Watkins, Howard::::::::: (1989)
On stage dignitaries included: Fresno County Board of Supervisors' Chair Vernon Conrad, Judge Frank Creed, Former Sheriff Hall McKinney and several others with current Sheriff Steve Magarian at lectern